Políticas curriculares: a luta pela significação no campo da disciplina História - Ana de Oliveira (Universidade do Minho, 2012)
This article focuses on the performance of the History disciplinary community in the interface that this community establishes with the teaching of this subject and with the curricular policies in Brazil in the 1980s. Based on the matrix of the conception of curriculum that understands as most important the concepts of power and culture, I combine the theoretical-methodological contributions of the History of School Disciplines with other notions, concepts and categories borrowed from Discourse Theory. I present how, in the Brazilian case, a significant number of social actors were involved in multiple processes of articulation and expressed, in texts and through discourse, different tendencies related to the teaching of the discipline History. Finally, I raise possible questions and issues as a result of my analysis of the Decree Law number 43/2007 which, in Portugal, establishes rules regarding the Master Degree in the Teaching of History and the Teaching of Geography, while at the same time I highlight the tension between the disciplines History and Social Studies.